Serosurvey of Avian Influenza Viruses (H5, H7, and H9) and Associated Risk Factors in Backyard Poultry Flocks of Lahore District, Pakistan - Chaudhry, Mamoona; Rashid, Hamad Bin; Thrusfield, Michael; Eisler, Mark C.; Welburn, Susan C. (Frontiers in Veterinary Science, 2021)
In Pakistan, rural poultry comprises 56% of the total poultry population in the country; however, epidemiological information about avian influenza viruses (AIVs) in these backyard flocks is lacking. A cross-sectional survey of villages of Lahore district was conducted from July - August 2009 using two-stage cluster sampling with probability proportional to size sampling to estimate seroprevalence and associated risk factors. Randomly 35 clusters, out of 308 villages of Lahore were selected, and from each cluster, six chickens of age >2 months were selected. A total of 210 serum samples were collected and examined by the haemagglutination inhibition test for specific antibodies against AIV subtypes H5, H7 and H9. Overall weighted seroprevalence of AIVs (any subtype), subtype H5, H7 and H9 was 65.2% (95%CI: 55.6 - 74.8%), 16.9% (95% CI: 10.8 - 23.0%), 0% (95% CI: 0-1.7%) and 62.0% (95% CI: 52.2 - 71.8%), respectively. Average flock size was 17.3 birds, and the main purpose of keeping poultry was for eggs/meat (70.6%, 95%CI: 59.7-81.4). The majority of them reared in a semi-caged system (83%, 95% CI: 74.5-91.3). Backyard birds received from different sources; that is, purchased from market, received as gift from friends or from any NGO, were 5.7 times more likely to become AI seropositive than those not exposed (CI 95%: 2.0-716.0). Bird that were kept in a backyard close to live-bird retail-shop were 6.9 times more likely to become AI seropositive compared to those that did not (CI 95%: 2.5-18.7). To reduce the risk of AIV in Pakistan, continuous surveillance of backyard poultry would be needed.